Composition of salivary microbiota in elderly subjects - Ogawa, Taiji; Hirose, Yujiro; Honda-Ogawa, Mariko; Sugimoto, Minami; Sasaki, Satoshi; Kibi, Masahito; Kawabata, Shigetada; Ikebe, Kazunori; Maeda, Yoshinobu (Scientific reports, 2018)
Frailty is gaining attention worldwide with the aging of society. Despite the potential lethality and multiple signs and symptoms in affected individuals, preclinical detection of early manifestations leading to frailty syndrome have not been established. We speculated that the composition of the oral microbiota is associated with general frailty, as well as a relationship between gut microbiota and general health condition. In the present study, we investigated the salivary microbiota composition in samples from healthy and frail elderly individuals using 16S rRNA sequencing analysis for characterization. We found a significant difference in diversity between elderly individuals living in a nursing home (EN) and healthy control (HC) subjects, as well as in the microbiota composition at the phyla level. A supervised orthogonal partial least squared discriminant analysis (OPLS-DA) revealed a significant difference in clear classification trend between the EN and HC groups, with all observations falling within the Hotellings T 2 (0.95) ellipse, with model fitness parameters of R 2 (cum) = 0.937 and Q 2 (cum) = 0.888, respectively. In addition, the score plots by unsupervised principal component analysis (PCA) showed a clear classification trend in both groups. Our findings suggest that general frailty is associated with oral microbiota composition and formation.